Modeling the financial and clinical implications of malaria rapid diagnostic tests in the case-management of older children and adults in Kenya. - Zurovac, D; Larson, B; Skarbinski, J; Slutsker, L; Snow, R; Hamel, M (2008)
Using data on clinical practices for outpatients 5 years and older, test accuracy, and malaria prevalence, we model financial and clinical implications of malaria rapid diagnostic tests (RDTs) under the new artemether-lumefantrine (AL) treatment policy in one high and one low malaria prevalence district in Kenya. In the high transmission district, RDTs as actually used would improve malaria treatment (61% less over-treatment but 8% more under-treatment) and lower costs (21% less). Nonetheless, the majority of patients with malaria would not be correctly treated with AL. In the low transmission district, especially because the treatment policy was new and AL was not widely used, RDTs as actually used would yield a minor reduction in under-treatment errors (36% less but the base is small) with 41% higher costs. In both districts, adherence to revised clinical practices with RDTs has the potential to further decrease treatment errors with acceptable costs.